1994
DOI: 10.1111/j.1600-9657.1994.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Accidental damage to incisors amongst Irish adults

Abstract: Evidence of accidental damage to permanent incisor teeth was recorded as part of a national survey of adult dental health in Ireland. A total of 746 adults aged between 16 and 34 years were examined. The prevalence of injury was considerably higher in males and the majority of subjects in both sexes had just one tooth affected. There was a continuing increase in prevalence with age which appeared to level out after the age of 24. A high level of untreated injuries was noted in both age groups; of those injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
2
14
2
1
Order By: Relevance
“…The maxillary central incisors were the most affected (n = 59). The frequency of fractured teeth was lower than in other studies conducted with living people …”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…The maxillary central incisors were the most affected (n = 59). The frequency of fractured teeth was lower than in other studies conducted with living people …”
Section: Discussioncontrasting
confidence: 74%
“…In the present study, the reports of 58 bodies (10.8%) showed the presence of TDI. These data showed a slightly lower prevalence than in the population‐based studies conducted with 16‐ to 50‐year‐olds, which vary from 13.5% to 28.1% . The affected teeth include the upper premolars, upper and lower canines, and upper and lower incisors.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Results from many studies demonstrate that the majority of TDIs occur in childhood and adolescence. It is estimated that 71–92% of all TDIs sustained in a lifetime occur before the age of 19 years (12, 31–33); other studies have reported a decrease after the age of 24–30 years (13, 34). Because of an increase in the number of older people in many countries and because most of these people are still in possession of their own teeth, there might be an increase in TDIs in older generations as a result of accidental falls.…”
Section: Background Factorsmentioning
confidence: 99%